Hubungan Stres Hospitalisasi Dengan Kuantitas Tidur Anak Di Rsu. Dr.Wahidin Sudiro Husodo Mojokerto - Atu Rokhmah, Assafik; Santoso, Windu (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractHospitalizations constitutes an unpleasant experience for children, who suddenly have to leave the familiar place of their home and the persons who are important for them, and stop their favorite activities, including playing (kourkourikos,2015). This leads to impaired fulfillment of resting sleep in children. The purpose of this reaserch was to find out the relationship of hospitalization stress with the quantity of child sleep in kertawijaya room RSV Dr. Wahidin Sudiro Husodo Mojokerto The research design is non experimental correlation of cross sectional approach. The population of all children who are hospitalized in Kertawijaya Room RSUD Dr. Wehidin Sudiro Husodo Mojokerto, which in january2017 amounted to 125 children. obtained a sample of 30 children were taken by the method of concecutive sampling independent variable is stress of hospitalization and dependent variable is quantity of child sleep. Data were taken using a modified DASS-42 questionnaire and tested for reliability validity. After data collected done.the data were processing with result of research most of children experiencing severe stress 63,33% (19 children) and almost all children less infulfill the quantity of sleep 83,3% (25 children). Furthermore, statistical test using spearman correlation test with spssversion 20 With result p (0,000) < a (0,05), so I IO is rejected, it means that is relationship between hospitalization stresswith children sleep quantity. Changes in the environment from home to hospital, separation and changes in physical conditions make hospitalization will cause a stress response in children. Stress will cause some physicological response such as difficulty sleeping. Therefore, it is necessary to increase the role of family and nurse to decrease the stress of hospitalization as well as fulfill the quantity of child sleep during hospitalization.Keywords:hospitalization, quantity of sleep, Stress